Mitteleuropäische Schulen IV (ca. 1380-1400); Textband Hofwerkstätten König Wenzels IV. und deren Umkreis - Theisen, Maria (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
The catalog is dedicated to those manuscripts of the Austrian National Library which were commissioned by King Wenceslas IV (1361-1419) and the Prague court. It forms a unit together with the catalog "Central European Schools III (Bohemia - Moravia - Silesia - Hungary, ca 1350-1400)" published in 2004, and completes the investigations concerned with the art of book illumination in the Central and Eastern regions during the second half of the 14th Century.